Legal Reform as Corruption Prevention Efforts in Management of Oil and Gas Upstream Business Field - Cahyani, Indah; Suastuti, Eny; Djulaeka; Murni; Hasanah, Uswatun (International Journal of Psychosocial Rehabilitation, 2020)
The main problem in this study is that transparency in the oil and gas business is still not implemented. This is because oil and gas regulations still have the potential for corruption. The purpose of this study is to examine the oil and gas regulations that have the potential for corruption. This study uses the concept approach and the statute approach. Researchers discovered that the upstream oil and gas management rules are not consistent wit h the general principles of good governance The results of the study concluded that the existence of potential regulations on the emergence of corruption include overlapping regulations in the field of licensing and private contractual relations allowing transparency to other parties. The researcher recommends that legal reform efforts are needed through licensing policies as a preventive instrument, the issuance of national energy policies, and effective monitoring of oil and gas exploitation.